2016
DOI: 10.1103/physrevlett.117.233903
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Shaping for Control of Nonlinear Propagation

Abstract: We study the nonlinear optical propagation of two different classes of light beams with space-varying polarization-radially symmetric vector beams and Poincaré beams with lemon and star topologies-in a rubidium vapor cell. Unlike Laguerre-Gauss and other types of beams that quickly experience instabilities, we observe that their propagation is not marked by beam breakup while still exhibiting traits such as nonlinear confinement and self-focusing. Our results suggest that, by tailoring the spatial structure of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 27 publications
4
67
0
Order By: Relevance
“…The usual fragmenta-tion of scalar vortex (OAM) beams in Kerr media can be inhibited by using vector vortex or FSL beams. It has been shown that cylindrical vector (CV) beams can additionally propagate with no change to their axially symmetric polarization distribution, while lower order (ℓ = 0, 1) FSL beams experience a polarization rotation [14]. We note that azimuthally polarized, spatial, dark soliton solutions of Maxwell's equations without OAM have been demonstrated in [33].…”
Section: Nonlinear Propagationmentioning
confidence: 96%
See 4 more Smart Citations
“…The usual fragmenta-tion of scalar vortex (OAM) beams in Kerr media can be inhibited by using vector vortex or FSL beams. It has been shown that cylindrical vector (CV) beams can additionally propagate with no change to their axially symmetric polarization distribution, while lower order (ℓ = 0, 1) FSL beams experience a polarization rotation [14]. We note that azimuthally polarized, spatial, dark soliton solutions of Maxwell's equations without OAM have been demonstrated in [33].…”
Section: Nonlinear Propagationmentioning
confidence: 96%
“…Obviously for more exact measurements, the rotation can be measured and compared at many points across the beam. In the simulations reported below, we have selected P 0 = 7.4mW, I sat = 5W cm −2 , n 2 = 8 × 10 −6 cm 2 /W and λ = 780nm that reproduce the experimental configuration given in [14]. We use a beam waist of 100µm throughout (unless explicitly stated otherwise), corresponding to a Rayleigh range of approx.…”
Section: Nonlinear Propagationmentioning
confidence: 99%
See 3 more Smart Citations